Evaluation of Budding and Field Planting Periods for Teak Seed Orchard Establishment - Vakshasya, Rajnish K.; Rawat, M. S. (Indian Forester, 1985)
The present study provides valuable information about the optimum time of budding and out planting of the prebudded stumps in field, under local condition, that is March and July respectively. The statistical approach of recommending the findings minimises the chances of arriving at deviated result at different places of the country. The study is indespensable to all who are engaged in tasks of Teak Seed Orchard establishment for necessary guidance.